The cost of dual-task walking: Cognitive demands restrict gaze behaviour and gait planning - Yuri Russo; Jiaxi Ye; Sarah E. Lamb; Amy Gear; William Lyon; Jinying Qiu; Millie Banks; Emily Martin; Zijing Wang; Maha Alghamdi; Phaedra Leveridge; William R. Young (PLoS ONE, 2026)
Adaptive walking relies on proactive gaze behaviour to plan foot placement and maintain stability. This study examined how mental workload and task complexity affect gaze behaviour and gait biomechanics during a precision target-stepping task in healthy young adults. We also quantified the frequency of cross-stepping during the experimental task. Twenty-three participants (18–23 years) walked along an L-shaped pathway containing raised stepping targets under single-task (ST) and dual-task (DT) conditions. Targets had four different layouts to create high and low difficulty conditions. Eye movements were recorded using mobile eye-tracking, and gait kinematics were recorded via motion capture. Compared with ST, DT walking produced slower walking speeds, longer stance times, and reduced velocity between stepping targets, indicating a more inefficient gait strategy. In addition, eye-tracking analyses revealed fewer and shorter fixations on task-relevant targets and a greater number of fixations directed toward task-irrelevant areas and, saccadic amplitudes were reduced despite increased outside fixations, suggesting a breakdown in visual exploration between proximal and distal regions of the walkway. In ST conditions, cross-stepping was more frequent than in DT. These findings indicate that increased mental workload compromises proactive gaze behaviour, likely through working-memory and attentional limitations that disrupt feedforward gait planning. Contrary to expectation, cross-stepping occurred more often during ST than DT walking, suggesting that in this population cross-stepping may not be a maladaptive strategy. Overall, these results highlight the cognitive demands of adaptive walking even in young, low-risk individuals and underscore the importance of preserving visual–motor coordination under cognitive stress.